2017
DOI: 10.7448/ias.20.1.21514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the feasibility and uptake of a community‐led HIV testing and multi‐disease health campaign in rural Uganda

Abstract: Introduction: Multi-disease community health campaigns can be effective for population-wide HIV testing in a research setting (SEARCH: NCT01864603). We sought to evaluate feasibility and uptake of a community-led health campaign (CLHC) planned and implemented by village leaders and local clinic workers in Uganda.Methods: Over five months in 2014, locally elected village leaders and Ministry of Health (MoH) clinic staff in a rural parish in Uganda planned a census followed by a CLHC, after training by two SEARC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This has revealed the poor quality of diabetes care, especially in insulin-dependent patients, and has helped to build a database of diabetics in the area. In Uganda [ 76 , 77 ] and South Africa [ 67 ], community-based HIV testing campaigns also included screening and diagnosis for diabetes and other NCDs, which also, parenthetically, helped to reduce the stigma associated with persons who had HIV. This intervention identified new diabetic patients and the intervention in Uganda [ 76 ] achieved a 63% linkage of care to newly diagnosed diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
“…This has revealed the poor quality of diabetes care, especially in insulin-dependent patients, and has helped to build a database of diabetics in the area. In Uganda [ 76 , 77 ] and South Africa [ 67 ], community-based HIV testing campaigns also included screening and diagnosis for diabetes and other NCDs, which also, parenthetically, helped to reduce the stigma associated with persons who had HIV. This intervention identified new diabetic patients and the intervention in Uganda [ 76 ] achieved a 63% linkage of care to newly diagnosed diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, only 5% of selected studies (n = 1) was a randomized controlled trial (RCT)—a pragmatic cluster RCT [19]. Most studies were either descriptive, cross sectional studies (n = 8) [20, 21, 22, 23, 24, 25, 26, 27] or observational cohort studies (n = 6) [21, 28, 29, 30, 31] (See S1 Dataset )…”
Section: Resultsmentioning
confidence: 99%
“… 1 Reference numbers [22], [26], [38] 2 Reference numbers [22], [24], [25], [26], [27], [29], [30], [31], [32], [33], [34], [35], [37] 3 Reference numbers [27] 4 Reference numbers [22], [24], [30], [32], [33], [35] 5 Reference numbers [22], [26], [30], [32], [34] 6 Reference numbers [23], [30], [32], [33], [34], [39] 7 Reference numbers [19], [20], [21], [23], [25], [31], [33], [38] 8 Reference numbers [25], [26], [36], [37], [39] 9 Reference numbers [25], [26], [34], [36], [37], [39] 10 Reference numbers [34], [39]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite them being unpopular, for these districts with a high prevalence but struggling to meet ART coverage targets it's still worth to invest in wide spread mopup community HIV testing campaigns with a leading role for health care workers [17]. These HIV testing campaigns can be conducted as part of health fairs or multi-disease screening campaigns/events to reduce stigma associated with HIV testing [18,19]. Studies have shown a high interest in HIV self-testing from a wide range of subgroups, including sero-discordant couples, men, young people, sex workers and their partners [20].…”
Section: Main Text District Based Hiv Testing Strategiesmentioning
confidence: 99%